If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.75(x + 5) = 12 Reorder the terms: 0.75(5 + x) = 12 (5 * 0.75 + x * 0.75) = 12 (3.75 + 0.75x) = 12 Solving 3.75 + 0.75x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3.75' to each side of the equation. 3.75 + -3.75 + 0.75x = 12 + -3.75 Combine like terms: 3.75 + -3.75 = 0.00 0.00 + 0.75x = 12 + -3.75 0.75x = 12 + -3.75 Combine like terms: 12 + -3.75 = 8.25 0.75x = 8.25 Divide each side by '0.75'. x = 11 Simplifying x = 11
| -9x-21=35x | | m-1=-2-9 | | 5w^2-23w-42=0 | | s=L-rL | | 2x-36=5(x+3) | | 100=20t+5t^2 | | 4-5X=59 | | 4x-3x=1x | | 6a^2-5a-4=0 | | 5x=6x+31 | | 25.00x=4.50 | | 3y-2+6x=0 | | 2x-6=3x+1-x-2 | | 4x^2+4x=9 | | 2(x+4)-5=2x+13 | | n+5=9+2n-3-8 | | .5(4x-10)=52+3x | | 69=3v | | 3x-6+x+8=42 | | 5xy^2+3xy^2= | | -5w^2+23w-42=0 | | 11=4x-3y | | 0=-16t^2+50t+6 | | 5x-4=3x+2x+3-2+1 | | 72=5c+7c-2c | | n+5=-1-16 | | 2(-3a+5)=2y+3 | | 68=4v | | a(a^7+1)-7(a^7+1)=0 | | 4x-3=x-3+3x | | 3(4)-6+4+8=42 | | m+5=1 |